2007
DOI: 10.1097/01.anes.0000267529.71756.f0
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Intubation in Patients with Cervical Spine Immobilization

Abstract: These findings demonstrate the utility of the Airtraq laryngoscope for tracheal intubation in patients with cervical spine immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 30 publications
6
119
3
4
Order By: Relevance
“…After obtaining approval by the Galway University Hospitals Research Ethics Committee (Galway, Ireland), we re-analysed data from six previously published clinical trials from our group that compared the Pentax AWS, Airtraq and Glidescope laryngoscopes with the Macintosh laryngoscope [14,16,17,[20][21][22]. The analysis was restricted to studies from our group in order to ensure standardisation of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…After obtaining approval by the Galway University Hospitals Research Ethics Committee (Galway, Ireland), we re-analysed data from six previously published clinical trials from our group that compared the Pentax AWS, Airtraq and Glidescope laryngoscopes with the Macintosh laryngoscope [14,16,17,[20][21][22]. The analysis was restricted to studies from our group in order to ensure standardisation of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…[10] A study of anesthetized patients with manual inline axial stabilization to limit cervical spine mobility showed improved glottic view and reduced duration of intubation attempts when comparing Airtraq OL and direct laryngoscopy with a Macintosh blade. [11] In fact, clinical situations with limited cervical spine mobility, while problematic for direct laryngoscopy, do not adversely influence Airtraq OL as optimal patient position for intubation using this device was found to be inline head and neck position. [12] No studies compared cervical spine motion using Storz VL instead of direct laryngoscopy.…”
Section: Discussionmentioning
confidence: 95%
“…9 Maharaj CH et al studies have demonstrated that the Airtraq reduces the difficulty of tracheal intubation in patients undergoing cervical spine immobilisation with MILS when compared with the Macintosh laryngoscope. 11 Koh et al reported higher success rate of intubation with Airtraq in patients with cervical immobilisation with collar. 12 Arslan et al evaluated the effectiveness of the Airtraq in patients with simulated cervical spine injury after application of a rigid cervical collar.…”
Section: Discussionmentioning
confidence: 98%